2021
DOI: 10.18203/2349-3933.ijam20213719
|View full text |Cite
|
Sign up to set email alerts
|

A case of acute limb ischemia

Abstract: Thromboembolism is a well-recognized complication of hematological malignancy. The incidence of symptomatic thrombosis at diagnosis is relatively low in AML (acute myeloid leukemia) patients, though its incidence increases on treatment with anthracyclines. We reported a case of 69 year old female with T2DM who presented with DVT and later on acute limb ischemia of the same lower limb. On hematological evaluation, she had leukocytosis and thrombocytopenia. Further evaluation revealed AML. Thromboembolism as a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…This more commonly involves the respiratory and central nervous systems and less frequently leads to cardiac, renal, or gastrointestinal complications [ 1 , 3 , 4 ]. Only seldom in the last two decades has leukostasis‐related acute limb ischemia been described [ 5 , 6 , 7 , 8 , 9 ]. This rare clinical manifestation is ultimately associated with high mortality and amputation risks [ 9 ].…”
Section: Subject Matter Backgroundmentioning
confidence: 99%
“…This more commonly involves the respiratory and central nervous systems and less frequently leads to cardiac, renal, or gastrointestinal complications [ 1 , 3 , 4 ]. Only seldom in the last two decades has leukostasis‐related acute limb ischemia been described [ 5 , 6 , 7 , 8 , 9 ]. This rare clinical manifestation is ultimately associated with high mortality and amputation risks [ 9 ].…”
Section: Subject Matter Backgroundmentioning
confidence: 99%
“…The decomposition in these wetlands creates a remnants layer offering anaerobic or aerobic substrates to support and grow bacteria that consume Se oxyanions as their energy source. [ 88 ] Se‐laden wastewater is treated in constructed wetlands by combining different mechanisms such as adsorption on sediments within wetlands, chemical transformation, and microbial reduction, and plant uptake. [ 41 ] Carvalho and Martin have found that aquatic plants like cattails ( Typha domingensis ), hydrilla ( Hydrilla verticillata Royle), duckweed ( Lemna obscura Aust.)…”
Section: Selenium Separation and Resource Recovery Technologiesmentioning
confidence: 99%
“…The rapid growth of industries has raised serious concerns about water scarcity and pollution. 1 One of the primary sources of water pollution comes from dyes, heavy metals and organic pollutants. The removal of heavy metals, which are not biodegradable, from wastewater is especially important.…”
Section: Introductionmentioning
confidence: 99%